2000
DOI: 10.1046/j.1365-2362.2000.0300s3076.x
|View full text |Cite
|
Sign up to set email alerts
|

New mechanisms of adrenostatic compounds in a human adrenocortical cancer cell line

Abstract: Our data demonstrate that adrenostatic compounds not only act by suppression of steroidogenic enzymes but can also influence both ACTH-R expression and cell proliferation in adrenal cells. As these effects occur in vitro at concentrations that are reached during treatment with these drugs in patients, they are probably also of clinical relevance. Particularly the antiproliferative activity of ETO may be useful in Cushing's syndrome due to adrenocortical cancer. The interaction of steroidogenesis, ACTH-R and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…After ACTH stimulation, H295R cells showed biphasic patterns of DHEA-S secretion. This biphasic reaction to ACTH has been reported previously (Jefcoate et al 1987;Le Roy et al 2000) and was explained by the biphasic upand downregulation of ACTH receptors in H295R cells (Fassnacht et al 1998(Fassnacht et al ,2000. This was reproduced also in a forskolin stimulation experiment (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…After ACTH stimulation, H295R cells showed biphasic patterns of DHEA-S secretion. This biphasic reaction to ACTH has been reported previously (Jefcoate et al 1987;Le Roy et al 2000) and was explained by the biphasic upand downregulation of ACTH receptors in H295R cells (Fassnacht et al 1998(Fassnacht et al ,2000. This was reproduced also in a forskolin stimulation experiment (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…These results are in line with the results obtained by Fassnacht et al, showing CYP11B1 inhibiting effects for ETO at low concentrations (IC 50 15 nM), while at higher concentrations ETO also inhibited CYP11A1 (IC 50 400 nM), resulting in decreased levels of all steroids as observed here for 1 μM ETO. 42 This latter study also reported CYP11A1 inhibiting effects for MET with an IC 50 of 17 μM. The observed decrease in levels of pregnenolone, 17α-OHpregnenolone, and 17β-testosterone in the present study for 10 μM MET are thus in line with these previous findings.…”
Section: Evaluating the Effects Of Model Chemicals On Steroidogenesissupporting
confidence: 92%
“…At higher doses, etomidate blocks side chain cleavage enzyme. More recent work has not only shown etomidate to potently block 11b-hydroxylase and side chain cleavage enzyme but also aldosterone synthase and may have anti-proliferative effects on adrenal cortical cells (16,17). Therefore, etomidate also has therapeutic relevance for aldosterone blockade and anti-tumorigenesis for metastatic adrenocortical tumours.…”
Section: Etomidatementioning
confidence: 99%